To set up the equations for the ages of Tony and Andrea, let's define:
- \( a \): Tony's current age
- \( a - 6 \): Andrea's current age (since Andrea is 6 years younger than Tony)
In two years, Tony will be \( a + 2 \) years old, and Andrea will be \( (a - 6) + 2 = a - 4 \) years old.
According to the problem, in two years, Tony will be three times as old as Andrea. Therefore, we can write the equation:
\[ a + 2 = 3(a - 4) \]
Now let's simplify the equation:
-
Distribute the 3 on the right side: \[ a + 2 = 3a - 12 \]
-
Rearrange the equation to isolate \( a \): \[ 2 + 12 = 3a - a \] \[ 14 = 2a \] \[ a = 7 \]
So, Tony's current age \( a \) is 7, and Andrea's current age is \( a - 6 = 1 \).
Now, looking at the original options you provided, the correct choice corresponds to the simplification we made:
The equation that equals \( a + 2 = 3(a - 4) \) from the problem is: \[ a + 2 = 3(a - 6 + 2) \] (Which simplifies to \( a + 2 = 3(a - 4) \).)
So, the correct response is: a + 2 = 3(a - 6 + 2).